Low T-cell reactivity to TDP-43 peptides in ALS - Ramachandran, Swetha; Grozdanov, Veselin; Leins, Bianca; Kandler, Katharina; Witzel, Simon; Mulaw, Medhanie; Ludolph, Albert C.; Weishaupt, Jochen H.; Danzer, Karin M. (Frontiers in Immunology, 2023)
Background Dysregulation of the immune system in amyotrophic lateral sclerosis (ALS) includes changes in T-cells' composition and infiltration of T cells in the brain and spinal cord. Recent studies have shown that cytotoxic T-cells can directly induce motor neuron death in a mouse model of ALS and that T cells from ALS patients are cytotoxic to iPSC-derived motor neurons from ALS patients. Furthermore, a clonal expansion to unknown epitope(s) was recently found in familial ALS and increased peripheral and intrathecal activation of cytotoxic CD8+ T cells in sporadic ALS.Here, we show an increased activation of peripheral T cells from patients with sporadic ALS by IL-2 treatment, suggesting an increase of antigen-experienced T cells in ALS blood. However, a putative antigen for T-cell activation in ALS has not yet been identified. Therefore, we investigated if peptides derived from TDP-43, a key protein in ALS pathogenesis, can act as epitopes for antigen-mediated activation of human T cells by ELISPOT and flow cytometry. We found that TDP-43 peptides induced only a weak MHCI or MHCII-restricted activation of both naïve and antigen-experienced T cells from healthy controls and ALS patients. Interestingly, we found less activation in T cells from ALS patients to TDP-43 and control stimuli. Furthermore, we found no change in the levels of naturally occurring auto-antibodies against full-length TDP-43 in ALS.Conclusion Our data suggests a general increase in antigen-experienced T cells in ALS blood, measured by in-vitro culture with IL-2 for 14 days. Furthermore, it suggests that TDP-43 is a weak autoantigen.